A 54-Point Verbal-Performance IQ Discrepancy on the WISC-R: Cognitive Functioning of a Child from an Alternative School - D. Lapierre; C. M. J. Braun; L. Le Pailleur (Behavioural Neurology)
Marked WISC-R verbal-performance discrepancy commonly leads to the assumption that such children have brain pathology or cognitive disorders. Children without brain dysfunction may also exhibit wide discrepancy, but a discrepancy score of 30 is assumed to occur in only 2% of the population. The actual investigation presents an 11-year-old child showing a 54-point discrepancy between the two scales of the WISC-R. Results of wide ranging testing and other considerations strongly suggested that this child didn't manifest any kind of brain dysfunction. It was concluded that the particular academic environment of the child, an alternative school, exerted a very strong influence on her results on the WISC-R. This conclusion is furthermore supported by the results of a follow-up evaluation, done 1 year after the child has been transferred to a traditional school, which revealed a WISC-R verbal-performance discrepancy of only 12 points.